2012
DOI: 10.1177/1362361312453882
|View full text |Cite
|
Sign up to set email alerts
|

The association of quality of social relations, symptom severity and intelligence with anxiety in children with autism spectrum disorders

Abstract: Limited quality of social relations, milder symptom severity and higher intelligence were shown to account for higher anxiety levels in autism spectrum disorders. The current study replicated and extended earlier findings by combining these three determinants of anxiety in autism spectrum disorders in one study. The sample consisted of 134 school-aged children with autism spectrum disorders, of whom 58 (43%) had a co-morbid anxiety disorder according to the Diagnostic Interview Schedule for Children-Parent ver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
35
2
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 62 publications
(41 citation statements)
references
References 38 publications
3
35
2
1
Order By: Relevance
“…These results are consistent with other studies demonstrating that anxiety in ASD is related to an older age and higher levels of cognitive functioning (e.g., Eussen et al 2013; Gadow et al 2005; Mayes et al 2011). It may be that older children with ASD, and children with ASD who have higher levels of cognitive functioning, are more aware of their difficulties.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…These results are consistent with other studies demonstrating that anxiety in ASD is related to an older age and higher levels of cognitive functioning (e.g., Eussen et al 2013; Gadow et al 2005; Mayes et al 2011). It may be that older children with ASD, and children with ASD who have higher levels of cognitive functioning, are more aware of their difficulties.…”
Section: Discussionsupporting
confidence: 93%
“…The same applies for IQ, which may be even more complicated because the relation between IQ and anxiety in youth with ASD is not clear itself. That is, some studies found a positive association between IQ and anxiety (e.g., Gadow et al 2005; Eussen et al 2013), while others point to a negative association (e.g., White and Roberson-Nay 2009) or suggest a quadratic instead of a linear relation (van Steensel et al 2011). …”
Section: Introductionmentioning
confidence: 99%
“…Young adulthood is a high-risk developmental period for the onset of mental health conditions, particularly depression and anxiety, in this population (Farley et al, 2009; Hofvander et al, 2009). Moreover, research with children with an ASD has documented an association between lower quality social relationships and heightened levels of anxiety (Eussen et al, 2012; Mazurek & Kanne, 2010). …”
Section: Discussionmentioning
confidence: 99%
“…Adolescents with high-functioning ASD may know that they are different, but not know why or how to change (Tantam 2003). As a result, a significant number of adolescents with ASD are at-risk for a cascade of secondary psychopathology, including depression, anxiety, and suicidality (Eussen et al 2012;Ghaziuddin and Zafar 2008;Stewart et al 2006;Tantam 2003;White and Roberson-Nay 2009).…”
Section: Behavioral and Cortical Development In Adolescencementioning
confidence: 99%